Improvement on Resolution of Dimensional Visual Measurements. (2016) - Khalili, Khalil
Abstract: The resolving power of any digital measuring system is the main limiting factor influencing its final accuracy. Introducing noise to the system can improve the accuracy by changing the level of quantization; however, this may not be easy to employ in practice. For a digital weighing scale the method may be implemented by repeating measurement and addition of a random known weight to the object being weighed every time the weight is measured. The method may be called Multi-Measurement of a single quantity Using Noise (MMUN). The theory of the method has already been proved. The current papers employ the method for a particular application in which the area of an object is being measured by a vision system experimentally. The results of experimental measurements show improvement of the accuracy beyond the resolution of the measuring device.